Effect of compatibilization on the photo-oxidation behaviour of polyethylene/polyamide 6 blends and their nanocomposites. (February 2015) - Mistretta, M.C.; Fontana, P.; Ceraulo, M.; Morreale, M.; La Mantia, F.P.
Abstract: Polymer based nanocomposites are increasingly attracting interest from academia and industry, and the use of polymer blends as matrices greatly increase their potential field of application. In order to improve their characteristics, the use of compatibilizers acting on the blend components is mandatory. However, this also leads to rising concerns regarding the behaviour of polymer blend based nanocomposites upon being subjected to photo-oxidative degradation. It is known that morphology can deeply influence the photo-oxidative behaviour, and this can be therefore deeply influenced by the blend components and by the use of compatibilizers. In this work, polymer blend nanocomposites, based on low density polyethylene and polyamide 6 have been prepared, containing organically modified clay as nanosized filler and two different functionalized polymers as compatibilizers, and processed in a film blowing operation in order to evaluate the effect of the compatibilization on photo-oxidation. The presence of the compatibilizer significantly improves the photo-resistance of the blend, while this improvement is less relevant in the nanocomposites since the photo-oxidation rate seems to be mainly dependent on the clay content and its direct effects on the photo-oxidative phenomena.